Penerapan Metode Six Sigma Untuk Perbaikan Kualitas Di PP Sinar Tani Palembang - Ixnatius; Achmad Alfian (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2019)
Quality improvement helps companies increase sales and reduce costs, both of which can increase profitability. PP Sinar Tani Palembang is a manufacturing industry engaged in rice milling. Quality control is still very lacking, this is indicated by the data from the scales which entirely pass the prescribed standards of 5 Kg, 10 Kg and 20 Kg. defective products: for 5 Kg packaged rice as much as 0.585 or 58.5%, 10 Kg rice as much as 0.604 or 60.4% and 20 Kg rice as much as 0.612 or 61.2%. It can be seen from the percentage of PP Sinar Tani Palembang every month experiencing a loss of 21,363 Kg or 1,068 kg per day with a nominal value of Rp 228,390.00 per month. By using the Six Sigma method, it is found that there are 2 factors that cause this loss is the occurrence of excess when filling and the balance scales of shear/oil scales used do not have accuracy so that the results of the scales all exceed the specified limit. One proposal that can be done is to replace the balance scales/shear scales/oil scales with digital scales so that the measuring results are more accurate. There was a decrease in the percentage of defects, namely for the weight of 5 kg from 0.585 to 0.166; weight of 10 kg from 0.604 to 0.145; weight of 20 kg from 0.612 to 0.139. Whereas from DPMO the increase from 2 sigma to 3 sigma.